The Effects of Childhood Separation: A Study on Mental Health - Josenberger, Taya; Griffin, Cole; Castle, Rebekah (Kansas State University. Dept. of Sociology, Anthropology and Social Work, 2020)
This study examines the impact of child separation at the US/Mexico border.Since 2016, immigration has been a large part of the republican policy platform and has led to policies like ending DACA and the “zero tolerance” policy, researched here. This research will study the trauma responses of migrant children who were separated at the border as well as the trauma responses of parents who have had their children taken from them by US border agents. It is important to know how a country’s immigration policy affects those it targets and include data about mental health in those discussions. Our study contributes to that data. Participants will be examined via a mixed-method trauma questionnaire and an in-person interview. This data will then be compared to the surveyed“control group” made up of immigrant families in similar detention centers that are still intact. This is done to limit extraneous variables. We expect to find that separation intensifies trauma associated with migrant detainment in both parents and children. This knowledge will fortify the advocacy for the well-being of immigrants in hopes of ending family separation and the “zero tolerance” policy at large. Findings can be used to hold lawmakers accountable for their actions and contribute to the discussion on immigration on a global level.
Kirmser Undergraduate Research Award - Group category, grand prize
Keywords: Childhood Separation; Mental Health; Mexico Border; DACA; Deferred Action for Childhood Arrivals; Immigration Policy; Migrant Children